Probiótico fúngico para ovinos alimentados com dietas de alto grão - Fabino Neto, Ronaildo (2019)
The objective was to select facultative anaerobic fungi from the sheep rumen and to evaluate their probiotic capacity in association with high grain diets (DAG) for Santa Inês/Dorper sheep. It was obtained 30 fungal isolates from the sheep rumen submitted to DAG, which were part of the fungal collection stored in the Laboratory of Microbiology of the Federal Goiano Campus Ceres Institute, where the in vitro and in vivo assay was also conducted. The isolates were classified according to morphotyping by microculture, submitted to amylase and mycotoxin enzyme production tests, tolerance to the main volatile fatty acids, viability in the ruminal fluid and the colonization capacity of the starch granules. In the performance test, 4x2 factorial was used in CED, with four inoculants (no inoculum, Rhizomucor spp., Aspergillus terreus and mixed of two fungi) and two processing (ground or whole grain). Eight bays with five lambs/bay were used for 75 days with 15 days of adaptation. The diets with 85% corn plus 15% vitamin, mineral and protein nucleus were fed ad libtum twice a day (7h and 16h), allowed to be left over 5%, and the inocula sprinkled at the time of feeding. Five samples were taken of the ingredients of the diets, the diets and the leftovers of the diets during the test to perform the centesimal analyzes. The animals were weighed biweekly for evaluation of performance indices. At the end of the trial, the carcass yields of five animals per treatment were calculated, as well as the ruminal fluid for the study of the microbiological profile of the rumen, macroscopic evaluation of the ruminal liquid, ammonia nitrogen concentration and microbiological activity, in addition to the TGI fragments for histological analysis. The parametric data were submitted to ANOVA and the data averages compared by the Tukey test at 5%. For the variables of the microbiological profile, the non-parametric tests, Chi-square test, Wilcoxon and Kruscall-Wallis were used, besides the descriptive analyzes. Of the 30 selected fungal isolates, 21 are of the genus Aspergillus, six of the genus Rhizopus spp. and three Rhizomucor spp. which were evaluated for their probiotic potential in vitro. All the isolates were able to degrade starch, and 19 are mycotoxin producers, being initially not feasible as a probiotic. There was no interaction between probiotic and processing factors for the performance variables (P>0.05), nor was there any effect of the addition of probiotics on the performance of sheep fed the different treatments (P> 0.05). Greater consumption of DM, MM, EE, NDF and CNF was observed for animals fed whole grain corn (MGI) (P<0.05). There was no significant difference (P>0.05) for OM, PB, GPMD, CA and neither for food efficiency. Fluid staining showed a low rate of acidosis. The aromatic odor predominated, which characterizes environment with neutral pH. Fluid samples showed high microbial activity. The ruminal pH differed (P<0.05) when considered the type of processing, being higher for milled grain (MGM). No difference was observed in any of the analyzed microbiological communities (P>0.05) (Lac + and Lac- bacteria, fungi, yeasts and protozoa). Six genera of facultative anaerobic fungi were identified for all ruminal fluid samples from a total of 15 observations. Cladosporium spp. was the most prevalent genus (46.66%), followed by Aspergillus (26.66%). There was no significant difference in the protozoan population (P>0.05). The width of the base of the papillae presented expressive interaction between the fungal probiotic and processing factors, being higher for MGM (P<0.05) for Rhizomucor spp. treatment and control (P<0.05). Selected anaerobic fungi from the rumen are promising to be used as a probiotic on a high grain diet, however in the performance assay the increased fungi concentration has not been shown to be effective. Other studies are necessary to find the appropriate situation for maximum productive expression of the isolated selected fungi.